Effects of postgrazing residue on morphogenetic and structural characteristics of Tifton 85 pastures - Da Silva, Wilton Ladeira [UNESP]; Malheiros, Euclides Braga [UNESP]; Reis, Ricardo Andrade [UNESP]; Sobrinho, Américo Garcia Da Silva [UNESP]; Ruggieri, Ana Cláudia [UNESP] (Universidade Estadual de Londrina, 2016)
The ideal time to start grazing is when pastures reach 95% light interception. The use of residual leaf area index (rLAI) to time the interruption of grazing under intermittent grazing has recently been studied in forage species in different climatic conditions in Brazil. However, studies evaluating the formation and development of leaves and tillers through morphogenetic and structural variables in functional rLAI are still lacking for Tifton 85 pastures. Therefore, the objective of this study was to evaluate the effects of varying rLAI in successive grazing cycles on morphogenetic and structural characteristics of Tifton 85 pasture grazed intermittently by sheep. Morphogenetic and structural characteristics were evaluated in three grazing cycles under three rLAI conditions (0.8, 1.6, and 2.4). The regrowth interval (time taken to return to 95% light interception) of pastures increased from 21.33 to 29.66 days with decreasing rLAI. The leaf appearance rate increased at a rate of 0.02 leaves tiller-1 day-1 and the number of live leaves per tiller increased by 0.41 with decreasing rLAI. Phyllochron, leaf elongation rate, final leaf length, leaf senescence rate, and stem elongation rate decreased linearly with decreasing rLAI. The number of live leaves per tiller was lower (7.97) in the third grazing cycle, probably owing to the higher senescence rate observed that same cycle, while the other variables had higher values. The 2.4 rLAI condition promotes excessive stem elongation, reduced leaf appearance, lower number of live leaves per tiller, and increased senescence of leaves, while the 0.8 and 1.6 rLAI conditions promote desirable morphogenetic and structural characteristics, which correlate directly with forage quality. In order to avoid excessive forage losses, grazing must occur preferentially by the end of March, when climatic conditions still support the appropriate development of the plants.
Keywords: Grazing cycles; Leaves appearance; Light interception; Residual leaf area index; Stem elongation